Nephrolepidina morgani (Lemoine & R. Douvillé, 1908) from the Oligo-Miocene of Decontra section (Majella, Central Apennines) - Schiavinotto, Francesco (Journal of Mediterranean Earth Sciences, 2015)
Abstract A Nephrolepidina population, coming from the Oligo-Miocene outcrop of the Bolognano formation near Decontra (Majella Mt., Central Apennines), is investigated applying the biometric analysis of the embryo-nepionic chambers and of the fifth stage of the neanic equatorial chamberlets, supplying additional data about parameters and factors that had already demonstrated to have taxonomic-biostratigraphic significance. "Embryonic-Nepionic Acceleration" is detected. The population can be referred to the evolutionary stage of N. morgani (Lemoine and Douvillé). The data evidence that the "Degree of stolonic distalization" (Factor FD5) and the "Shape Index" (Factor SI5), at the 5th neanic stage of the population, have a very good fitting with the previously evidenced overall trend to modify the shape of the equatorial chamberlets, connected with a gradually more distal position of the radial stolons ("Neanic Acceleration"). The previous Chattian age of the upper part of the Lepidocyclina Limestone of the Bolognano formation can be better specified on the basis of the biometric data obtained here, with a correlation with the larger Foraminifera SBZ23 Biozone. The specific, phylogenetic and biostratigraphic definitions could be improved by means of further integration of the embryonic-nepionic-neanic data.